Whiplash Injuries Can be Visible by Functional Magnetic Resonance Imaging - Bengt H Johansson (Pain Research and Management)
Whiplash trauma can result in injuries that are difficult to diagnose. Diagnosis is particularly difficult in injuries to the upper segments of the cervical spine (craniocervical joint [CCJ] complex). Studies indicate that injuries in that region may be responsible for the cervicoencephalic syndrome, as evidenced by headache, balance problems, vertigo, dizziness, eye problems, tinnitus, poor concentration, sensitivity to light and pronounced fatigue. Consequently, diagnosis of lesions in the CCJ region is important. Functional magnetic resonance imaging is a radiological technique that can visualize injuries of the ligaments and the joint capsules, and accompanying pathological movement patterns.